ALIMENTAR SEMIZLIKNING XAVF OMILLARI - Xasanov Mirzaolim Ilyosbek o'g'li (NAZARIY VA AMALIY FANLARDAGI USTUVOR ISLOHOTLAR VA ZAMONAVIY TA’LIMNING INNOVATSION YO’NALISHLARI, 2025)
Alimentary obesity is a common metabolic disorder resulting from improper nutrition and a sedentary lifestyle. This article analyzes the main risk factors of alimentary obesity, including the consumption of high-calorie foods, lack of physical activity, genetic predisposition, stress, and hormonal imbalance. Additionally, the impact of these risk factors on the body and preventive measures aimed at reducing obesity are discussed.